THE VALUE OF THE PROJECT, ITS HISTORICAL CONTEXT AND MEANINGFUL - Liezina , A.V. (The actual problems of regional economy development, 2017)
In the article the historical stages of the category of “value” in various sciences, particularly in project management were considered. Chronology of evolutionary change and borrowing the term “value” in various sciences was developed. Existing approaches to determining the value of project management were analyzed. Author's interpretation of value projects was represented. Author's vision “iron” triangle of project management criteria based on the transformation of the classical approach was represented. Substance of the value of projects, taking into account the interests of all stakeholders, in terms of their value expectations was revealed.